Changes in Ecological Relationships of Argali Magars - Khattri, Man Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2006)
In this article I have looked the relationships of inter-ethnic and inter-ecological gradients, which mediated by social-cultural mechanism i.e. ista mitra (fictive kin relationship). Ista has played role to with local production and different socio-cultural of two different ecological setting. It tries to demonstrate how socio-cultural processes transform when rice gets closer market access. The ethnographic data suggest to argue that fictive kin relationship is caused by the multiple uses of rice began in Argal. Similarly, social and geographical relationships are developed on the basis of cultural institution like kinship; but its limitation varies according to culture of an ethnic group. I argue that not only the state rules and regulations, market system but also with the internal changes brought the present social cultural system in Argal. DOI: 10.3126/dsaj.v1i0.276 Dhaulagiri Vol.1 (2005) pp.67-86